Final-Year Dental Students' Opinions of their Training in Medical Emergency Management. Issue 1 (March 2014) - Bell, G; James, H; Kreczak, H; Greenwood, M
The management of medical emergencies is clearly of vital importance in dental practice. The starting point of training in this area is the undergraduate dental degree programme. The aim of this study was to examine the opinions of final-year dental students at Newcastle School of Dental Sciences in relation to their undergraduate training in medical emergency management. Overall the responses were positive but the need for further practical training in the use of emergency drugs and equipment was highlighted.